THU0535 Title: safety and efficacy of platelet-rich plasma in treatment of carpal tunnel syndrome; a randomised controlled trial. (12th June 2018) - Bagherzadeh, L.; Raeissadat, S.A.; Karimzadeh, A.; Hashemi, M.
Abstract : Background: Carpal tunnel syndrome is the most common peripheral entrapment neuropathy, for which conservative treatments are the first measures taken but they are not usually sufficient. Objectives: Recently major attention has been drawn to platelet-rich plasma, for its possible effects on axon regeneration and neurological recovery. Although few studies have evaluated the effects of this treatment in carpal tunnel syndrome, further investigations are required to reach concrete conclusion. Methods: In this randomised controlled trial, women referring to the physical medicine and rehabilitation clinic at Shahid Modarres Hospital during 2016 with a diagnosis of mild and moderate idiopathic carpal tunnel syndrome were included and randomly assigned to two groups of control, only using a wrist splint, and platelet-rich plasma that received wrist splints along with a single local injection of platelet-rich plasma. The outcome measures were assessed via Visual Analogue Scale, the Boston Carpal Tunnel Syndrome Questionnaire and electrophysiological findings including the peak latency of sensory nerve action potential and the onset latency of the compound muscle action potential. Results: A total of 41 women were included and randomly assigned to two groups of control (20 wrists) and platelet-rich plasma (21 wrists). Before treatment there were no significant differences between the two groups except for the median peak latency of sensory nerve action potential which was significantly higher among the patients in the platelet-rich plasma group (p=0.03). All the measured variables significantly decreased in both groups after 10 weeks of treatment except for the median onset latency of the compound muscle action potential (p=0.472). Finally, the changes in neither of the outcome measures evaluated were found to significantly differ between the two groups, even when the analyses were adjusted for age of the patients. Conclusions: The findings of this study showed that in a relatively short period of time after treatment, a single injection of platelet-rich plasma in the wrist does not add significantly to the effects of conservative treatment with wrist splints, in regards to the women pain and symptom severity, functional status and electrophysiological parameters. Disclosure of Interest: None declared